Evaluation of left ventricular function in diabetics with ischemic heart disease - Hassan, Affan E.; Mohammed, Najeeb H.; Al-Janabi, Hamid K.; Abbas, Asaad A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Diabetes mellitus is a major risk factor for coronary artery disease, with a higher incidence of myocardial infarction and sudden death. Left ventricular dysfunction is difficult to diagnose and to differentiate into diastolic and systolic dysfunction on the basis of medical history, physical examination, electrocardiography (ECC) and chest radiography. Two-dimensional, M-mode, and Doppler echocardiography are excellent for diagnosing left ventricular dysfunction. M-mode echocardiography was used for diagnosing left ventricular systolic dysfunction, while Doppler echocardiography has become well accepted as a reliable, reproducible and practical noninvasive method for the diagnosis of left ventricular diastolic dysfunction.Subjects and methods: eighty four (84) males, type 2 diabetic patients with ischemic heart disease, their mean age was 60 ± 7 years, in addition to fourty six (46) non diabetics again with ischemic heart disease matched for sex and age served as control were involved in this study. Each patient was subjected to medical history, clinical examination, blood pressure measurement, physical measurement, lipid profile estimation, ECG, chest x-ray, M-mode and Doppler echocardiography to assess their left ventricular function, whether they suffer left ventricular diastolic dysfunction or systolic dysfunction and or combined systolic and diastolic dysfunction.Results: The result of this study demonstrated that diabetic subjects were more prone to develop ST elevation myocardial infarction and isolated diastolic dysfunction of impaired relaxation type (74%). However, echocardiography clarify that small percentage of those patient suffer an isolated systolic dysfunction (26%).Conclusion: Higher percent of diabetic subjects suffer ST elevation myocardial infarction and they were found to develop diastolic dysfunction.